PENGARUH KUALITAS PRODUK HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN NESMILO DI SAMARINDA - Rabiah Rabiah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This study aims to examine the effect of product quality, price and sevice quality on costumer satisfaction Nesmilo restaurant in Samarinda. The population in this study were consumers in Nesmilo restaurants with a total sampel of 80 respondents. Data collection techniquess were carried out by observaction, interviews, documentation and questionnaires. Analysis tools used validity test, reliability test, classic assumption test, multiple linear regression analysis and hypothesis testing with spss version 22. The results of this study indicate that product quality, price and service quality simultaneously have a positive effect on customer satisfaction. The results of this study also indicate that product quality partially has a significant negative effect on customer satisfaction. The variable price partially has no effect on customer satisfaction, then the service quality partialy has a positive and significant effect on customer satisfaction and the most influential variable on customer satisfaction is sevice quality.